German residential real estate valuation under NGFS climate scenarios - Lucas Ter Steege; Edgar Vogel (Deutsche Bundesbank, 2021)
We combine data on real estate online listings and climate scenarios from the Network for Greening the Financial System (NGFS) to estimate changes in real estate valuations due to changing expectations about future energy costs. Using a simple theory of the relation between prices and energy consumption, we find that the most ambitious climate scenarios potentially come with significant impacts on real estate prices and thus the collateral value of inefficient homes. In the aggregate, losses in housing values and thus collateral could lie in the range of 11 to 13% of the aggregate housing value.
Keywords: R31; Q41; Q54; 330; Residential Real Estate; climate transition risk; climate scenarios; CO2 taxation